PERANCANGAN GALERI TIDUR INTERAKTIF DI JAKARTA PUSAT - Brianna Wijaya Utama; Denny Husin (Jurnal Sains, Teknologi, Urban, Perancangan, Arsitektur (Stupa), 2023)
In the last few decades, architecture has tended to be apathetic since aesthetics and function have been given more attention which has put the context of life aside. Architecture and empathy must go hand in hand so architects need to understand the spaces they design from the perspective of their users. Sleep disorders are problems in the quality and quantity of sleep that can cause stress and daytime sleepiness. Sleep disorders have a reciprocal relationship with mental health where sleep disorders can cause or be caused by mental illness. Since sleep disorder is a common thing in Indonesia, it leads to the normalization of sleep disorders which can cause a long-term negative impact on mental and physical health, lifestyle, work performance, social and economy. This design aims to provide a space that can increase awareness of sleep disorders as well as special therapy programs for sleep disorders through healing architecture. The benefit of this design is to provide a healing space for people with sleep disorders that focuses on the reception of the human senses on spatial quality. The design method used in this design is the everyday architectural method. The results of this design are interactive sleep gallery program, sleep-related research program, and special therapy programs for sleep disorders. Therapeutic programs are implemented so that people with sleep disorders can recover from sleep disorders in the long term by improving healthy lifestyle and creating good daily habits. Keywords: architecture; empathy; healing; mental; sleep Abstrak Beberapa dekade terakhir, arsitektur cenderung bersifat apatis karena estetika dan fungsi lebih diperhatikan yang membuat konteks kehidupan dikesampingkan. Arsitektur dan empati harus berjalan beriringan sehingga arsitek perlu memahami ruang yang mereka rancang dari perspektif penggunanya. Gangguan tidur adalah masalah dalam kualitas dan kuantitas tidur yang dapat menyebabkan stres dan kantuk di siang. Gangguan tidur memiliki hubungan timbal balik dengan kesehatan mental dimana gangguan tidur dapat menyebabkan atau disebabkan oleh penyakit mental. Umumnya gangguan tidur di Indonesia menyebabkan adanya normalisasi gangguan tidur yang dapat berdampak negatif secara jangka panjang pada kesehatan mental dan fisik, gaya hidup, performa bekerja, sosial, hingga ekonomi. Perancangan ini bertujuan untuk menyediakan ruang yang dapat meningkatkan kesadaran akan gangguan tidur serta program terapi khusus untuk gangguan tidur melalui healing architecture. Manfaat dari perancangan ini adalah untuk menyediakan ruang penyembuhan bagi penderita gangguan tidur yang berfokus pada resepsi indera manusia terhadap kualitas spasial. Metode perancangan yang digunakan dalam perancangan ini adalah metode arsitektur keseharian. Hasil dari perancancangan ini berupa program galeri tidur interaktif, program penelitian terkait tidur, serta program terapi khusus gangguan tidur. Program yang bersifat terapi diterapkan agar penderita gangguan tidur dapat memulihkan gangguan tidur secara jangka panjang dengan memperbaiki pola gaya hidup dan menciptakan kebiasaan sehari-hari yang baik.